2018
DOI: 10.1021/acs.est.8b01447
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Microcystins by Permanganate: pH and Temperature-Dependent Kinetics, Effect of DOM Characteristics, and Oxidation Mechanism Revisited

Abstract: Oxidative degradation of six representative microcystins (MCs) (MC-RR, -LR, -YR, -LF, -LW, and -LA) by potassium permanganate (KMnO; Mn(VII)) was investigated, focusing on the temperature- and pH-dependent reaction kinetics, the effect of dissolved organic matter (DOM), and the oxidation mechanisms. Second-order rate constants for the reactions of the six MCs with Mn(VII) ( k) were determined to be 160.4-520.1 M s (MC-RR > -LR ≈ -YR > -LF ≈ -LW > -LA) at pH 7.2 and 21 °C. The k values exhibited activation ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
6
25
0
Order By: Relevance
“…Our rate constant values for MC-LR and MC-RR are consistent and in the range observed by other researchers and follow the trend MC-RR > MC-LR > MC-LA (Table 1). Correcting for the temperature difference between our conditions and those reported by Kim et al [21] or Ding et al [26] would increase our values by eight percent. Sample data are shown in Figure 2.…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…Our rate constant values for MC-LR and MC-RR are consistent and in the range observed by other researchers and follow the trend MC-RR > MC-LR > MC-LA (Table 1). Correcting for the temperature difference between our conditions and those reported by Kim et al [21] or Ding et al [26] would increase our values by eight percent. Sample data are shown in Figure 2.…”
Section: Resultssupporting
confidence: 47%
“…Combining experiments (N=9) yielded an average second order rate constant at these conditions of 118 ± 9 M −1 · s −1 . This is approximately 25% lower than previously reported values by Kim et al [21] and Ding et al [26]. We also conducted a limited number of experiments with MC-RR and MC-LR.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Specific UV absorbance (SUVA), ascertained as the UV absorbance of a solution at a given wavelength normalized for DOC concentration, is strongly correlated with the degree of aromaticity of DOM (Weishaar et al, 2003). This indicator of DOM aromaticity is often calculated at 254 nm (SUVA 254 ) (Kim et al, 2018;Lee et al, 2018). Numerous studies have shown that the variation of the SUVA 254 descriptor is directly bound to metal complexation.…”
Section: Electronic Spectral Changesmentioning
confidence: 99%
“…As the soil has an alkaline pH, an increase of OHconcentration with the freezing concentration effect may take place. This pH increase might also affect the action of persulfate, since it is more efficient under acidic conditions (Fang 2013;Tang 2015), but not that of permanganate which is pH independent (Kim 2018;Waldemer 2006). In the case of ferrate, a pH increase may affect the molecular speciation of ferrate(VI).…”
Section: Resultsmentioning
confidence: 99%